(untitled) (International Journal of Innovative Technologies in Economy, 2025)
Digital financial technologies play a pivotal role in enhancing the efficiency of Islamic crowdfunding platforms. Technologies such as blockchain and smart contracts contribute to greater transparency and security, while artificial intelligence is employed to ensure compliance with Shariah principles through contract verification and the avoidance of prohibited elements such as riba. Islamic crowdfunding is founded on the principles of risk- and profit-sharing and provides innovative financing solutions such as murabaha and mudarabah, thereby supporting entrepreneurship and socially impactful projects. However, these platforms face significant challenges, including the absence of unified regulatory frameworks, security risks such as cyberattacks, and limited public awareness of Islamic financial tools. Conversely, promising opportunities emerge through the development of digital financial products such as electronic sukuk and the promotion of financial inclusion by expanding access to financial services, particularly in emerging markets. Case studies highlight the success of platforms such as Saudi Arabia’s “Ethraa” and Singapore’s “Capital Boost” in integrating technology with Shariah principles, leveraging tools like blockchain and digital payment systems.